2019
DOI: 10.1177/0267658319841403
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of syntactically unconstrained anaphors in Turkish heritage speakers

Abstract: Previous work has shown that heritage grammars are often simplified compared to their monolingual counterparts, especially in domains in which the societally-dominant language makes fewer distinctions than the heritage language. We investigated whether linguistic simplification extended to the anaphoric system of Turkish heritage speakers living in Germany. Whereas the Turkish monolingual grammar features a three-way distinction between reflexives ( kendi), pronouns ( o), and syntactically-unconstrained anapho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Pronominal resolution (i.e., establishing the relation between the anaphor and its antecedent) has been the subject of L3A studies, e.g., Gračanin-Yuksek et al (2020), andLago et al (2018), but we have not found previous studies where the non-complementary distribution of reflexive possessive and pronominal possessives was studied as the potential source of the syntactic CLI. Still, we will mention two studies which deal with the quirky distribution of possessive pronouns with implications for the languages involved in our main study.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Pronominal resolution (i.e., establishing the relation between the anaphor and its antecedent) has been the subject of L3A studies, e.g., Gračanin-Yuksek et al (2020), andLago et al (2018), but we have not found previous studies where the non-complementary distribution of reflexive possessive and pronominal possessives was studied as the potential source of the syntactic CLI. Still, we will mention two studies which deal with the quirky distribution of possessive pronouns with implications for the languages involved in our main study.…”
Section: Literature Reviewmentioning
confidence: 84%
“…As discussed earlier, local readings of ziji appear to be more frequent relative to LD readings, and processing local readings of ziji is easier than processing LD readings (see Dillon, 2014). Related to the ease of processing is Hawkins's (2004) proposal of 'Minimize domains', according to which the parser chooses the nearest antecedent for both syntactic and processing considerations (for work on LD reflexives in Turkish and Icelandic under this framework, see Gračanin-Yuksek et al, 2020;Putnam and Arnbjörnsdóttir, 2015). A similar concept, 'minimal distance', was proposed by Tsang (2009) to account for her finding that learners acquiring L3-Cantonese do not benefit from having an L1 that has LD reflexives.…”
Section: L2-acquisition Of Mandarin Ld Reflexivesmentioning
confidence: 99%
“…In linguistics, it is used to explain the structure, function, and use of language [3]. In the era of artificial intelligence, the study of paraphrasing meta-language not only helps to deeply understand the internal mechanism of language but is also of great significance for improving language processing techniques, such as natural language processing and machine translation [4][5]. In the era of artificial intelligence, paraphrase meta-language research can be strengthened by using big data technology, analyzing a large number of language samples, revealing the usage patterns and laws of language, building language models by computational modeling, simulating the process of language generation and comprehension by algorithms, and deepening the understanding of paraphrase meta-language by combining the research in the fields of computer science, cognitive science, and so on [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%